2012
DOI: 10.2174/15680096112091191
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phytochemicals in the Chemoprevention and Treatment of Hepatocellular Carcinoma: In Vivo Evidence, Molecular Targets, and Clinical Relevance

Abstract: Hepatocellular carcinoma (HCC), one of the most common and lethal cancers, is a growing menace in modern society. Until recently, the majority of detected cases of liver cancer have been found in the developing nations of Asia and Africa; however, its occurrence has significantly increased in the United States. HCC occurs due to several etiologies, such as alcoholism, dietary carcinogens, iron overload, viral hepatitis, as well as several hepatic chronic diseases. In view of the limited treatment options, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The use of phytochemicals obtained from dietary sources provides a novel and fascinating preventive and therapeutic approach against HCC. Dietary phytochemicals possess potent antioxidant and anti‐inflammatory properties that are extremely critical to combat the significant oxidative stress and inflammation implicated in liver cancer . In our previous studies, we have been confirmed the anti‐inflammatory properties, and the apoptosis‐inducing effects of γ‐mangostin in U87 MG, GBM 8401 and HT‐29 cell lines .…”
Section: Discussionsupporting
confidence: 65%
“…The use of phytochemicals obtained from dietary sources provides a novel and fascinating preventive and therapeutic approach against HCC. Dietary phytochemicals possess potent antioxidant and anti‐inflammatory properties that are extremely critical to combat the significant oxidative stress and inflammation implicated in liver cancer . In our previous studies, we have been confirmed the anti‐inflammatory properties, and the apoptosis‐inducing effects of γ‐mangostin in U87 MG, GBM 8401 and HT‐29 cell lines .…”
Section: Discussionsupporting
confidence: 65%
“…[8][9][10][11] Recently, identification of bioactive constituents from medicinal and dietary plants to suppress hepatic tumorigenesis is gaining considerable attention. [12][13][14][15][16] Marine algae have long been used as a fresh food with potential nutritional benefits and treatment for various disorders. 17 Various marine bioactive compounds such as phenolics, carotenoids, terpenoids, and polysaccharide sulfates, exhibit potent antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several anticancer drugs, such as vinblastine, teniposide, camptothecin, docetaxel, etoposide, and paclitaxel, have been either identified in natural sources or synthesized by modification of molecules having natural origins [6,7]. Numerous natural products, including phytochemicals of dietary and non-dietary origin, have been shown to modulate various signaling pathways linked to hepatocarcinogenesis in vitro and in vivo, which could be valuable for the prevention and treatment of HCC [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%